Modelling the effects of factors on the stated preference towards telecommuting in IIUM campus, Gombak - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (Routledge - Taylor & Francis Group, 2019)
The increase in number of private vehicles has not only taken place in central cities, but has also occurred in university campuses. High use of private vehicles by IIUM community is posing a strain on the ability of the existing road to cope with the increasing traffic volume and parking demand within the campus. Telecommuting is one of the Transportation Demand Management (TDM) measures that aimed at reducing peak hour traffic congestion by allowing commuters to work from home to save their driving time to work, and more importantly to eliminate some vehicle trips. The main objective of this paper is to estimate the effects of the factors on the choice of telecommuting. Three hundred respondents participated in this study through survey questionnaire, which has resulted in a response rate of 67.11%. Findings indicate that 29% and 19.2% of the academic and administrative staff preferred to telecommute, if they were given the option. Multinomial logistic regression was conducted to estimate the effects of socioeconomic, trip and work related factors on the preference to telecommute. Parameter estimates on the administrative employees’ preference to telecommute indicate that number of young children, frequency of face-to-face communication and frequency of using email were significant factors in predicting whether an individual is more inclined to choose ‘definitely yes’ towards performing telecommuting as compared to ‘not at all’. As for academic employees, delay time (home-workplace), frequency of face-to-face communication, frequency of using fax machine, frequency of using email and frequency of using mobile network were significant predictors for the preference of ‘definitely yes’ towards telecommuting as compared to ‘not at all’.